Interpretasi Nilai Kearifan Lokal Minangkabau dalam Lirik Lagu “Pasan Buruang” sebagai Upaya Penanaman Mitigasi Bencana dalam Pembelajaran Sosiologi - Dendy Marta Putra; Nurlizawati Nurlizawati (Universitas Negeri Padang, 2022)
This paper describes sociology learning that is integrated with the value of local wisdom in facing the challenges of living in a disaster area. One of the disasters that often occur and have a major impact on people's lives is flooding and banjir bandang (galodo). One way to deal with natural disasters is to understand how to deal with disasters, therefore it is necessary to understand disaster mitigation. Disaster mitigation education is an effort to overcome and minimize the impact if a disaster occurs, so it is important for teachers to teach disaster mitigation education, which will later be beneficial for students in interacting with the environment. One of the appropriate materials to teach disaster mitigation education is local wisdom material. The form of local wisdom that exists in Minangkabau is a song, one of the songs that contains the value of local wisdom in dealing with disasters is